2017
DOI: 10.1155/2017/6972732
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule, Big Prospects: MicroRNA in Pregnancy and Its Complications

Abstract: MicroRNAs are small, noncoding RNA molecules that regulate target gene expression in the posttranscriptional level. Unlike siRNA, microRNAs are “fine-tuners” rather than “switches” in the regulation of gene expression; thus they play key roles in maintaining tissue homeostasis. The aberrant microRNA expression is implicated in the disease process. To date, numerous studies have demonstrated the regulatory roles of microRNAs in various pathophysiological conditions. In contrast, the study of microRNA in pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 143 publications
(164 reference statements)
1
85
0
Order By: Relevance
“…Pregnancy itself is considered to be a diabetogenic endocrine-metabolic adaptation process, with altered glucose metabolism resulting in the progressive development of IR and consequent increased postprandial glucose, circulating lipids and beta-cell demand 35,36 . Beta-cell adaptation to pregnancy, increasing capacity through expansion of cell mass and secretion, is associated with alterations to the endogenous miRNA profile in response to the physiological changes of pregnancy 37 . Several islet microRNAs have been reported to contribute to this adaptive response, with effects on secretory activity and survival which are reversed after pregnancy 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy itself is considered to be a diabetogenic endocrine-metabolic adaptation process, with altered glucose metabolism resulting in the progressive development of IR and consequent increased postprandial glucose, circulating lipids and beta-cell demand 35,36 . Beta-cell adaptation to pregnancy, increasing capacity through expansion of cell mass and secretion, is associated with alterations to the endogenous miRNA profile in response to the physiological changes of pregnancy 37 . Several islet microRNAs have been reported to contribute to this adaptive response, with effects on secretory activity and survival which are reversed after pregnancy 38 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HHV-6A infection induced in endometrial cells the down-modulation of miR18, miR101-3p, miR181-5p, miR92, and miR1207-5p. Notably, miR18 expression was found to be decreased in circulating blood and placentas of women suffering from preeclampsia (PE) [27,28]; miR101-3p reduction was associated with trophoblast apoptosis [29] in PE placentas; decreased miR181-5p was reported in women with recurrent miscarriage [30], although other works reported a possible association between increased expression of miR181 and abnormal pregnancy, due to its role in attenuating the immunosuppressive properties of mesenchymal stem cells [31]; miR92, belonging to the miR17-92 cluster normally upregulated during implantation in receptive uteri [4], was reported to be downregulated in EPL placentas [26,32], and miR1207-5p down-regulation was reported in women with RIF compared with controls [5].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miRNAs are involved in reproductive regulation. Previous studies have also confirmed that multiple miRNAs are involved in reproductive regulation [10]. In the study of eclampsia, miR195 expression changes were related to physiological functions such as trophoblast invasion [1115].…”
Section: Introductionmentioning
confidence: 90%